2023
DOI: 10.55632/pwvas.v95i1.945
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid shape is sexually dimorphic

Abstract: Uniform assessment of the glenoid anatomy is fundamental in establishing uniform standards of care. Subjectivity in classification inherent in the absence of quantification permits deficiency in glenoid assessment methods (e.g., Walch classifications). Therefore, this report aims to objectively quantify the variance of glenoid fossa contours in both sexes via geometric morphometric techniques. A total of 135 glenoid fossae from 135 adult Mexican individuals, who had undergone CT scanning for non-shoulder-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Scapular morphology is highly variable across the human population (Dwight, 1887;Graves, 1921). The multi-factorial sources of scapular shape variation are unclear; however, previous work has revealed significant differences in scapular shape between males and females (Maranho et al, 2022;Scholtz et al, 2010;Zdilla and Guzmán-López, 2023). Understanding sexual dimorphism in scapular morphology is important for contextualizing scapula features that are correlated with injury risk (Lee et al, 2020), developing personalized treatments, identifying relevant shape traits for classifying sex in forensic analyses (Atamtürk et al, 2019;Dabbs and Moore-Jansen, 2010;Di Vella et al, 1994;Er et al, 2020;Peckmann et al, 2016), and providing insights into the role of sexual selection in human evolution (Puts, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scapular morphology is highly variable across the human population (Dwight, 1887;Graves, 1921). The multi-factorial sources of scapular shape variation are unclear; however, previous work has revealed significant differences in scapular shape between males and females (Maranho et al, 2022;Scholtz et al, 2010;Zdilla and Guzmán-López, 2023). Understanding sexual dimorphism in scapular morphology is important for contextualizing scapula features that are correlated with injury risk (Lee et al, 2020), developing personalized treatments, identifying relevant shape traits for classifying sex in forensic analyses (Atamtürk et al, 2019;Dabbs and Moore-Jansen, 2010;Di Vella et al, 1994;Er et al, 2020;Peckmann et al, 2016), and providing insights into the role of sexual selection in human evolution (Puts, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous geometric morphometric studies of the scapula have quantified morphology using 2D projections. These studies have found that the male scapula tends to have more pronounced curvature on the medial and lateral borders, a more projected inferior angle, and a more concave glenoid compared to the female scapula (Maranho et al, 2022;Scholtz et al, 2010;Zdilla and Guzmán-López, 2023). However, the 2D approach could be missing important sexually dimorphic 3D features.…”
Section: Introductionmentioning
confidence: 99%